Ab Initio Calculation on the Low-Lying Excited States of BSe(+) Cation Including Spin-Orbit Coupling (Journal of Atomic and Molecular Sciences, 2022)
The internally contracted multi-reference configuration interaction method(MRCI) with Davidson modification and the Douglas-Kroll scalar relativistic correctionis used to calculate $BSe^+$ ion at the level of aug-cc-PVQZ basis set. The calculatedelectronic states, including four triple and two quintuple $Λ$-$S$ states, are correlated tothe dissociation limit of $B^+(^1S_g)+Se(^3P_g)$ and $B(^2P_u)+Se+(^4S_u).$ The states of $^3Π$(II) and $^3Σ^-$(II) from the dissociation limit of $Se^+(^4S_u)+B(^2P_u)$ both have double well and spectroscopicproperties are studied. Various curve crossing are revealed, which could leadto the predissociation of the $X^3Π$ and $^5Π$ states and the possible predissociation pathwayare analyzed. Spin-orbit coupling interaction is taken into account via the stateinteraction approach with the full Breit-Pauli Hamiltonian operator, which causes theentire six $Λ$-$S$ states to split into 21 Ω states. This is the first time spin-orbit couplingcalculation of $BSe^+.$ The potential energy curves of the $Λ$-$S$ and Ω electronic states aredepicted with the aid of the avoided crossing rule between electronic states of the samesymmetry. Then the spectroscopic constants of bound $Λ$-$S$ and Ω states were obtained,which have never been observed in experiment.
Keywords: Potential energy curve; Spin-orbit coupling effect (SOC); Spectroscopic constants.